TECHNIQUE OF TESTING ON FRETTING AT THE SPHERE-TO-PLANE CONTACT - Khimko, А.; Smirnova, О. (Proceedings of National Aviation University (archive), 2012)
The methodology of conducting tests on fretting at the sphere-to-plane contact was developed for the wing mechanization unit, namely for screw-nut pair with intermediate balls. Wearability tests were conducted on a modified installation МФК-1, the feature of which is the designed holder that allows testing with real balls. It was found that at the dry contact of ШХ-15 and 30Х2НВФA materials, surface microcracks are formed due to welding of microasperities areas and their rupture under the influence of vibration.